ETHNOPHARMACOLOGICAL USES OF PLANTS AMONG TRIBAL AND RURAL FOLKS OF BANIHAL FOREST AREA OF KASHMIR - PARWEZ AHMAD; TARIQ A BUTT; MUDASIR BHAT; AMINUDDIN; NAQUIBUL ISLAM (International Journal of Pharma and Bio Sciences, 2012)
Banihal forest area falls in Pirpanjal mountainous range of Kashmir, an integral part of great Himalaya. The forest of Banihal is represented by good vegetation of which conifers are dominated ones. During ethnopharmacological exploration in the area, the survey team from Regional Research Institute of Unani Medicine, Srinagar-Kashmir collected and identified 63 plants species from the study area. Data on medicinal uses of 20 plants species was recorded by the team from the local tribal and rural folks. The information recorded for the treatment of different ailments has been presented in the paper so as to enrich the existing knowledge on ethnopharmacology.